Socialization of Cyber Bullying Prevention for Taman Rama Jimbaran Senior High School’s Students - Maria Osmunda Eawea Monny; Evelyn Angelita Pinondang Manurung; Eka Ayu Purnama Lestari (Law Doctoral Community Service Journal, 2022)
This social engagement is done in order to improve understanding of students Senior High School of Taman Rama Jimbaran about cyber bullying. This socialization is important to be implemented considering that students nowadays are really attached to their gadgets/devices. Besides, social media is also one of the media that mostly used by students to express their ideas or anything they have in their mind. This socialization is important because sometimes students considering that what they wrote or posted in social media is just something good. However, due to some extend it can be an unpleasing or humiliating others. Method in this social engagement is used was online conference through Zoom. Main findings of this social engagement are: the eagerness of the students to know the information about cyber bullying and the enthusiasm of principle and teachers as a form of their attention about cyber bullying and how to prevent it. The students were able to grasp the information by asking questions needed. There were 35 participants in this activity, those were Principle, teachers and students. Finally, the information about how to prevent cyber bullying, the impact for the victims and law implementation for those who did cyber bullying. Finally, it is expected that cyber bullying preventions are able to be applied properly and appropriately by students and parties involved in it.